A version of Putinar's Positivstellensatz for cylinders - Escorcielo, Paula Micaela (2020)
We prove that, under some additional assumption, Putinar's Positivstellensatz holds on cylinders of type S×R with S={x¯∈Rn|g1(x¯)≥0,…,gs(x¯)≥0} such that the quadratic module generated by g1,…,gs in R[X1,…,Xn] is archimedean, and we provide a degree bound for the representation of a polynomial f∈R[X1,…,Xn,Y] which is positive on S×R as an explicit element of the quadratic module generated by g1,…,gs in R[X1,…,Xn,Y]. We also include an example to show that an additional assumption is necessary for Putinar's Positivstellensatz to hold on cylinders of this type.